Graphite negative electrode material with excellent high-temperature cycle performance and preparation method thereof
By mechanically crushing and heat treatment of the raw material coke of the lithium-ion battery negative electrode material, a high-temperature resistant graphite negative electrode material was prepared, which solved the problem of poor performance of the negative electrode material at high temperature in the prior art, and achieved efficient and stable electrochemical performance.
Patent Information
- Application Number
- CN202411870679.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
Existing lithium-ion battery anode materials perform poorly at high temperatures, resulting in capacity attenuation and shortened cycle life, limiting their use range.
By mechanically crushing and intermittent shaping of the raw material coke, coke powder with a specific particle size and structure is obtained, and two heat treatments are performed, including pre-carbonization and graphitization treatments, high temperature-resistant graphite negative electrode material is prepared.
The prepared graphite negative electrode material exhibits excellent cycling performance and long-term stable operation ability at high temperatures, with high first charge and discharge efficiency, and a capacity retention rate of 300 weeks of 1P cycle at 60°C reaches 91%.
Smart Images

Figure CN119612506A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium battery negative electrodes, and in particular to a graphite negative electrode material with excellent high-temperature cycle performance and a preparation method thereof. Background Art
[0002] Lithium-ion battery energy storage systems have the advantages of fast response speed, high modularity, and recyclability. They show broad application prospects in renewable energy grid connection, microgrids, backup power supplies, etc. Although lithium-ion battery energy storage technology has developed rapidly, it still faces many challenges in practical applications, among which the impact of environmental factors is particularly significant. The performance of lithium-ion batteries is affected by environmental factors such as temperature and humidity, especially temperature. In high temperature environments, the capacity decay of lithium-ion batteries is accelerated, the cycle life is shortened, and even safety problems such as thermal runaway may occur. High-temperature areas such as deserts and tropical areas are rich in renewable energy resources such as solar energy and wind energy in my country and even the world. However, high temperature environments pose severe challenges to the reliability of lithium-ion battery energy storage systems. In order to make full use of the clean energy in these areas, it is urgent to develop lithium-ion battery energy storage systems that can operate stably under high temperature conditions.
[0003] At present, the negative electrode materials of commercial lithium-ion batteries are mainly graphite, of which natural graphite and artificial graphite are two common types. Natural graphite, as a cheap and readily available material, is widely used in lithium-ion batteries. The advantage of natural graphite is that it is abundant in reserves and has low cost. However, the particle size of natural graphite is inconsistent and there are many surface defects, so it is easy to react with the electrolyte, resulting in a decrease in cycle performance. From the perspective of expansion, the expansion rate of natural graphite is higher than that of artificial graphite. The main reason is that the crystallinity of flake graphite is high, the unitization of the layer structure is large, and it has obvious anisotropy. This structural feature is prone to irreversible structural changes at high temperatures, resulting in battery capacity decay. In order to accelerate the improvement of various electrochemical properties of lithium-ion batteries to meet actual needs, researchers are developing negative electrode materials based on artificial graphite. Compared with natural graphite, artificial graphite has the advantages of high crystallinity, uniform interlayer spacing, and small specific surface area. However, the preparation cost of artificial graphite is high, and there are still unresolved problems of capacity decay and shortened cycle life at high temperatures.
[0004] In order to improve the electrochemical performance of artificial graphite, a layer of carbon layer or other conductive materials is coated on the surface of graphite, which can effectively reduce the contact area between graphite and electrolyte, inhibit the formation of SEI film, and improve the cycle stability of the battery. However, due to the problem of coating non-uniformity, the surface coating layer of artificial graphite negative electrode materials prepared by the existing coating process peels off or decomposes at high temperatures, and has the defects of poor cycle performance and low initial charge and discharge efficiency during high temperature (35℃ / 60℃) charging and discharging. Therefore, artificial graphite negative electrodes are generally only used at room temperature, which limits their scope of use. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a graphite negative electrode material with excellent high temperature cycle performance to solve the defects of poor high temperature performance and limited operating temperature range of artificial graphite negative electrodes in the prior art.
[0006] The present invention is achieved by the following technical scheme: a method for preparing a graphite negative electrode material with excellent high temperature cycle performance comprises mechanically crushing and intermittently shaping the raw coke to obtain a particle size D50 of 6-20um and a tap density of 0.6-1.2g / cm 3 The coke powder is prepared by a first heat treatment to obtain a pre-carbonized material; the pre-carbonized material is placed in a crucible furnace, a box furnace, an inner series furnace, or a continuous graphitization furnace for a second heat treatment to obtain a graphitized material; the graphitized material is naturally cooled to room temperature, and is sieved and demagnetized using a 300-mesh vibrating sieving machine to obtain a high-temperature resistant long-cycle graphite negative electrode material.
[0007] Furthermore, optical structural analysis of the raw coke showed that the flaky and fibrous structures accounted for 50-90%.
[0008] Furthermore, the first heat treatment includes pre-carbonizing the coke powder in a high-temperature externally heated tunnel kiln, wherein the pre-carbonizing time is 9 to 12 hours and the heating temperature is 600 to 1200°C.
[0009] Furthermore, the temperature of the second heat treatment is 2000-3000° C., and the treatment time is 2-15 hours.
[0010] Another aspect of the present invention provides a graphite negative electrode material with excellent high temperature cycle performance, wherein the graphite negative electrode material is obtained according to the preparation method as described above.
[0011] Its electrochemical properties are as follows: the first discharge specific capacity is 325~340mAh / g, the first charge and discharge efficiency is 95%, and the capacity retention rate of 300 cycles at 1P at 60°C is 91%.
[0012] The present invention also provides a lithium battery, the negative electrode of which contains the graphite negative electrode material with excellent high temperature cycle performance as described above.
[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0014] 1. The present invention uses a special heat treatment process to enable the prepared graphite negative electrode material to maintain a stable structure and have the characteristics of high temperature resistance. This high temperature resistance ensures that the material will not degrade in performance at high temperatures, can operate stably for a long time, and adapt to high temperature working conditions.
[0015] 2. The graphite negative electrode material of the present invention has excellent electrochemical properties, and at the same time has a high initial charge and discharge efficiency and a high-temperature capacity retention rate of up to 300 weeks, which means that its electrochemical performance can remain stable, and after long-term use, the capacity of the negative electrode material has almost no attenuation, making the graphite negative electrode material of the present invention very suitable for application scenarios with high cycle requirements, such as electric vehicles, power storage systems, etc.
[0016] 3. The present invention precisely controls the structure of the raw material coke and the heat treatment process, and the final graphite negative electrode material obtained has higher performance and longer service life, and has high temperature stability, long cycle life, excellent electrochemical performance and structural stability, and can be widely used in multiple fields (such as electric vehicles, energy storage batteries, electronic equipment, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0018] Figure 1 This is a scanning electron microscope image of the graphite negative electrode material prepared in Example 1 of the present invention.
[0019] Figure 2 This is the XRD diagram of the graphite negative electrode material prepared in Example 1 of the present invention.
[0020] Figure 3 This is a curve chart of the first charge and discharge of a lithium battery prepared from the graphite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations. In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0022] Embodiment 1,
[0023] This embodiment discloses a method for preparing a graphite negative electrode material with excellent high temperature cycle performance, and the specific implementation scheme includes the following steps:
[0024] Optical structure analysis was used to analyze the coke with flaky and fibrous structures accounting for 65%.
[0025] After mechanical grinding and shaping by a shaping machine, a spherical particle intermediate product with an average particle size D50 of 11 μm is obtained.
[0026] The intermediate product is placed in a crucible and sent into a high-temperature externally heated tunnel kiln for pre-carbonization treatment. The residence time in 7 high-temperature zones is about 11 hours. The temperature in the high-temperature zones is about 1100°C, and finally a pre-carbonized material is obtained.
[0027] The pre-carbonized material is placed in a crucible furnace or a box furnace, heated to 2600°C, kept warm for 10 hours, naturally cooled to room temperature, and then sieved and demagnetized by a 300-mesh vibration sieving machine to obtain a graphitized single-particle artificial graphite negative electrode material.
[0028] Figure 1 A scanning electron microscope image of the graphite negative electrode material in this embodiment is shown.
[0029] Figure 2 The XRD pattern of the graphite negative electrode material in this embodiment is shown.
[0030] Figure 3 A curve chart showing the first charge and discharge of a lithium battery prepared from the graphite negative electrode material in this embodiment.
[0031] It can be seen from the three figures shown in this embodiment that the graphite negative electrode material in this embodiment exhibits excellent specific capacity and high coulombic efficiency during the first charge and discharge process, indicating that it has high efficiency and stable electrochemical properties and is very suitable for use in high-performance lithium-ion batteries.
[0032] Embodiment 2,
[0033] In this embodiment, coke with flaky and fibrous structures accounting for 65% is selected for optical structural analysis.
[0034] The raw coke is crushed by a mechanical mill and shaped by a shaping machine to obtain a spherical particle intermediate product with an average particle size D50 of 13 μm.
[0035] The intermediate product is placed in a crucible and sent into a high-temperature externally heated tunnel kiln for pre-carbonization treatment. The residence time in the seven high-temperature zones is about 9 hours. The temperature in the high-temperature zones is about 1000°C, and finally a pre-carbonized material is obtained.
[0036] The pre-carbonized material is placed in a crucible furnace or a box furnace, heated to 2500°C, kept warm for 11 hours, naturally cooled to room temperature, and then screened and demagnetized by a 300-mesh vibration screen to obtain a graphitized single-particle artificial graphite negative electrode material.
[0037] Embodiment 3,
[0038] The optical structure analysis selected in this embodiment is of coke in which the flaky and fibrous structures account for 51%.
[0039] The raw coke is crushed by a mechanical mill and shaped by a shaping machine to obtain a spherical particle intermediate product with an average particle size D50 of 17 μm.
[0040] The intermediate product is placed in a crucible and sent into a high-temperature externally heated tunnel kiln for pre-carbonization treatment. The residence time in 7 high-temperature zones is about 11 hours. The temperature in the high-temperature zones is about 1200°C, and finally a pre-carbonized material is obtained.
[0041] The pre-carbonized material is placed in a crucible furnace or a box furnace, heated to 2700°C, kept warm for 14 hours, naturally cooled to room temperature, and then screened and demagnetized by a 300-mesh vibrating screen to obtain a graphitized single-particle artificial graphite negative electrode material.
[0042] Embodiment 4,
[0043] In this embodiment, the optical structure analysis is performed on coke in which the flaky and fibrous structures account for 56%.
[0044] The raw coke is crushed by a mechanical mill and shaped by a shaping machine to obtain a spherical particle intermediate product with an average particle size D50 of 20 μm.
[0045] The intermediate product is placed in a crucible and sent into a high-temperature externally heated tunnel kiln for pre-carbonization treatment. The residence time in 7 high-temperature zones is about 11 hours. The temperature in the high-temperature zones is about 1200°C, and finally a pre-carbonized material is obtained.
[0046] The pre-carbonized material is placed in a crucible furnace or a box furnace, heated to 3000°C, kept warm for 3 hours, naturally cooled to room temperature, and then sieved and demagnetized by a 300-mesh vibration sieving machine to obtain a graphitized single-particle artificial graphite negative electrode material.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 2 is that the raw materials are crushed by a mechanical grinder and shaped by a shaping machine to obtain a spherical particle intermediate product with an average particle size D50 of 25 μm.
[0049] In this comparative example, the pre-carbonization treatment step was omitted, and the spherical particle intermediate product was directly placed in a crucible furnace, heated to 2700°C, kept warm for 14 hours, naturally cooled to room temperature, and then sifted and demagnetized by a 300-mesh vibrating sieving machine to obtain the graphite negative electrode material of this comparative example.
[0050] Comparative Example 2
[0051] The difference between this comparative example and Example 1 is that the raw materials selected in this comparative example are crushed by a mechanical grinder and shaped by a shaping machine to obtain a spherical particle intermediate product with an average particle size D50 of 24 μm.
[0052] In this comparative example, the pre-carbonization treatment step was omitted, and the spherical particle intermediate product was directly placed in a box furnace, heated to 2600°C, kept warm for 10 hours, naturally cooled to room temperature, and then sifted and demagnetized by a 300-mesh vibrating sieving machine to obtain the graphite negative electrode material of this comparative example.
[0053] Comparative Example 3
[0054] The difference between this comparative example and Example 3 is that the raw materials selected in this comparative example are crushed by a mechanical grinder and shaped by a shaping machine to obtain a spherical particle intermediate product with an average particle size D50 of 22 μm.
[0055] In this comparative example, the pre-carbonization treatment step was omitted, and the spherical particle intermediate product was directly placed in a crucible furnace and heated to 2700°C, kept warm for 14 hours, naturally cooled to room temperature, and then sifted and demagnetized by a 300-mesh vibrating sieving machine to obtain the graphite negative electrode material of this comparative example.
[0056] Experimental example
[0057] The graphite negative electrode materials in the above embodiments and comparative examples were made into batteries and subjected to performance tests. The battery performance table of the graphite negative electrode materials obtained is shown in Table 1.
[0058] Table 1. Battery performance of ink negative electrode materials
[0059] Serial number First discharge capacity mAh / g First charge and discharge efficiency (%) Capacity retention rate after 300 cycles at 1P at 60℃ (%) 1C discharge capacity retention rate after storage at 60℃ for 30 days (%) Capacity retention rate after 300 cycles at 1P at 70°C (%) 1C discharge capacity retention rate after storage at 70℃ for 30 days (%) Example 1 340.5 94.41 95.3 92.4 92.1 88.1 Example 2 326.1 94.85 95.6 91.5 90.3 87.3 Example 3 329.5 95.39 95.5 91 91.1 86.8 Example 4 337.1 94.25 95.7 92 90.7 86.2 Comparative Example 1 336.2 94.78 92.5 92.8 87.1 80.9 Comparative Example 2 319.1 93.92 92.2 90.5 82.4 80.3 Comparative Example 3 323.7 94.44 90.5 91 83.4 82.3
[0060] It can be seen from the above table that the graphite negative electrode material synthesized by the preparation method proposed in the present invention still shows high cycle performance and high retention rate at 60°C, and further it can be seen that the graphite negative electrode material prepared by the preparation method of the present invention has good high temperature resistance.
[0061] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a graphite negative electrode material with excellent high temperature cycle performance, characterized in that: The preparation method comprises: The raw coke is mechanically crushed and intermittently shaped to obtain a particle size D50 of 6-20um and a tap density of 0.6-1.2g / cm 3 coke powder, and subjecting the coke powder to a first heat treatment to obtain a pre-carbonized material; The pre-carbonized material is placed in one of a crucible furnace, a box furnace, an inner series furnace, and a continuous graphitization furnace for a second heat treatment to obtain a graphitized material. The graphitized material is naturally cooled to room temperature, sieved and demagnetized using a 300-mesh vibrating sieving machine to obtain a high-temperature resistant long-cycle graphite negative electrode material.
2. The method for preparing a graphite negative electrode material with excellent high temperature cycle performance according to claim 1, characterized in that: Optical structural analysis of the raw coke shows that the flaky and fibrous structures account for 50-90%.
3. The method for preparing a graphite negative electrode material with excellent high temperature cycle performance according to claim 1, characterized in that: The first heat treatment comprises, The coke powder is pre-carbonized by a high-temperature externally heated tunnel kiln. The pre-carbonization treatment time is 9 to 12 hours, and the heating temperature is 600 to 1200°C.
4. The method for preparing a graphite negative electrode material with excellent high temperature cycle performance according to claim 1, characterized in that: The temperature of the second heat treatment is 2000-3000° C., and the treatment time is 2-15 hours.
5. A graphite negative electrode material with excellent high temperature cycle performance, characterized in that: The graphite negative electrode material is obtained according to the preparation method described in any one of claims 1 to 4, The electrochemical performances are as follows: The first discharge specific capacity is 325~340mAh / g, the first charge and discharge efficiency is 95%, the capacity retention rate of 1P cycle 300 weeks at 60℃ is 95%, and after being placed at 60℃ for 30 days, the 1P discharge capacity retention rate at room temperature is 91%.
6. A lithium battery, characterized in that: The negative electrode thereof contains the graphite negative electrode material having excellent high temperature cycle performance as claimed in claim 6.
Citation Information
Cited By
High-tap-density hard carbon material as well as preparation method and application thereof
CN122166753A